Seismic Response of a Concrete Frame with Weak Beam-Column Joints. Issue 1 (February 2015) - Bayhan, B.; Moehle, J. P.; Yavari, S.; Elwood, K. J.; Lin, S. H.; Wu, C. L.; Hwang, S. J.
A reduced-scale, planar, two-story by two-bay reinforced concrete frame with weak beam-column joints was subjected to earthquake simulations on a shaking table. The beam-column joints did not contain transverse reinforcement, as is typical in older construction designed without attention to detail for ductile response. A series of linear and nonlinear analytical models of the frame were developed in accordance with American Society of Civil Engineers standards and subjected to the input base motions. The goodness of fit between analytical and measured results depended on the details of the analytical model. Reasonably accurate reproduction of the measured response was obtained only by modeling the inelastic responses of both columns and beam-column joints. The results confirm the importance of modeling nonlinear joint behavior in older concrete buildings with deficient beam-column joints.